2019
DOI: 10.1111/ijfs.14223
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cyanide content of bitter almond and its oil using different treatments

Abstract: Summary To reduce the cyanide content of bitter almond oil, four treatments were investigated. The optimal parameters were obtained, under which loss of cyanide of 79.4%, 87.2%, 98.3% and 98.4% were achieved for baking, microwave, water boiling and ultrasonic treatment, respectively. The effects of treatments on the physicochemical properties of bitter almond oil showed no significant differences. All treatments could reduce the cyanide content in bitter almond oil, and ultrasonic treatment was the most optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Further, evidence that ultrasonic treatment reduced the cyanide content in bitter almond oil obtained by solvent extraction process has been provided by Zhang et al. (2019).…”
Section: Almond Oil Extraction Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Further, evidence that ultrasonic treatment reduced the cyanide content in bitter almond oil obtained by solvent extraction process has been provided by Zhang et al. (2019).…”
Section: Almond Oil Extraction Methodsmentioning
confidence: 89%
“…A recent study by showed that autoclaving treatment before ultrasound-assisted oil extraction increased the oil recovery by 8.69%, without affecting the almond oil composition. Further, evidence that ultrasonic treatment reduced the cyanide content in bitter almond oil obtained by solvent extraction process has been provided by Zhang et al (2019).…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tube was stirred for 1 min and kept in a water bath at 50 °C for 1 h. Finally, the solution was diluted to 10 mL with distilled water and left to stand for 30 min. [ 44 ] The supernatant was collected and subjected to gas chromatography coupled with mass spectrometry (GC‐MS) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the composition of EOs represents the final image including the respective biosynthetic fingerprint but also the modified substances due to preceding processing. Furthermore, in some cases, individual compounds are intentionally removed because of their toxicity, such as hydrogen cyanide from bitter almond oil or methyl eugenol from rose oil ( Rusanov et al, 2012 ; Zhang et al, 2019 ). One important modified oil, e.g ., by increasing the cineole content, while reducing the acid content, is eucalyptus oil ( European Medicines Agency, 2014 ).…”
Section: Production Of Eosmentioning
confidence: 99%